2009
DOI: 10.1142/s0129167x09005637
|View full text |Cite
|
Sign up to set email alerts
|

Equations of the Moduli of Higgs Pairs and Infinite Grassmannian

Abstract: In this paper the moduli space of Higgs pairs over a fixed smooth projective curve with extra formal data is defined and is endowed with a scheme structure. We introduce a relative version of the Krichever map using a fibration of Sato Grassmannians and show that this map is injective. This, together with the characterization of the points of the image of the Krichever map, allows us to prove that this moduli space is a closed subscheme of the product of the moduli of vector bundles (with formal extra data) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…We also note that many topics of this paper have been studied by the Salamanca school of algebraic geometers from yet another point of view [2,7,9,22].…”
Section: Cymentioning
confidence: 99%
“…We also note that many topics of this paper have been studied by the Salamanca school of algebraic geometers from yet another point of view [2,7,9,22].…”
Section: Cymentioning
confidence: 99%
“…In particular, in the papers [33,34,35] it was shown that, the so-called Schur pair plays a central role in the construction and analysis of Krichever map. With all the diversity of the results obtained, the constructions associated with the Krichever map share a common feature, namely, an algebraic curve, though closely connected, is, essentially, an object exterior to Sato Grassmannian except, probably the rather formal papers [36,20]. It seems that there are very few results concerning the study of algebraic curves in Sato Grassmannian itself.…”
mentioning
confidence: 99%
“…It should be noted that the main scope of the paper is a search of concrete algebraic curves and corresponding families in the specific Birkhoff strata of Sato Grassmannian in contrast to the general and formal description addressed in the papers [34,36,20,33,35].…”
mentioning
confidence: 99%